Pengembangan Pendidikan Formal: Studi Kebijakan Kepemimpinan Kiai di Pondok Pesantren Tarbiyatul Ummah Muaro Jambi - Khalik Khalik; Bawaihi; Ayu Yulianti (JMiE (Journal of Management in Education), 2021)
This research is based on a strong tendency in pesantren to consolidate institutional organizations, particularly on aspects of leadership and management. This research uses descriptive qualitative methods by reviewing the kiai leadership policy in the development of formal education at SMP IT Pondok Pesantren Tarbiyatul Ummah Muaro Jambi. The results showed that kiai policy in the development of formal education was carried out by adjusting the conditions of boarding schools and considering various ideas / suggestions to be mutually agreed upon. While in formulating its policy, kiai involves all administrators of educational institutions and gives authority to implement policies that have been decided. The implementation of the policy is socialized through meetings with institutions to strengthen the flow of information on the policies to be implemented.